Developing creative thinking of pedagogical staff of general secondary education institutions - Nizhnik, O. (Problems of Engineer-Pedagogical Education, 2019)
The article emphasizes the necessity to improve qualifications of employees of general secondary education institutions in the context of the implementation of the «New Ukrainian School» Concept, and highlights the need to develop their creative thinking. Different ways of enhancing teachers’ professional competencies are revealed, with the emphasis being on the technology «workshop», which is described in the article as an active developmental group interaction, aimed at boosting creative potential and disclosing certain abilities or skills. The task of the workshop is to initiate a discussion, motivate the participants to share valuable methodological findings, thoughts and beliefs, activate the group and mediate between the participants, optimize the process of obtaining knowledge and finding solutions. The expediency is substantiated and the technology of the workshop aimed at the development of creative thinking of employees of general secondary education institutions is worked out, the realization of which is carried out on the motivational-target, content-procedural, and evaluative-reflexive stages. The choice of ways to work with teachers within the developed technology is explained. Thus, at the first motivational-target stage among the ways of developing a positive attitude to mastering creative thinking, the following ways are highlighted: giving examples, activation of independent search for ways of forming creative thinking, testing, analysis, self-analysis, and design. The content-procedural stage is realized through the following methods of acquiring knowledge and mastering skills of creative thinking such as work in pairs and small groups, role-playing, business games, active and interactive methods of interaction of participants, modeling, active listening, practical work, roundtables, mini-lectures, «penetration» of an insignificant declaration of knowledge, discussions, etc. The tasks of the evaluative-reflexive stage of the technology of the developed workshop are realized by means of methods of control and self-control, among which there are observation, oral questioning, written analysis and self-analysis, self-evaluation, collective evaluation, and collective discussion of results. The suggested technology of the workshop aimed at the development of creative thinking of employees of general secondary education institutions results in the need for further research for its experimental verification.